Development of hydrocolloid microgels as starch granule mimetics: Hydrogel particles fabricated from gelatin and pectin. (December 2015) - Wu, Bi-cheng; McClements, David Julian
Abstract: In this study, hydrocolloid microgels fabricated by electrostatic complexation of gelatin and pectin were developed as possible starch mimetics. The impact of covalent cross-linking on the physicochemical and structural properties of the microgels was investigated. Microgels were formed by acidifying a mixture of gelatin (0.5 wt.%) and pectin (0.01 wt.%) from pH 10 to 5 at 40 °C, followed by cross-linking with glutaraldehyde (0 to 2 mM). At low glutaraldehyde levels (< 0.5 mM), cross-linking occurred primarily within the microgels and did not affect particle dimensions, whereas at high levels (2 mM), cross-linking connected adjacent microgels leading to the formation of large flocs. Rheological and microscopic analysis showed that the degree of cross-linking impacted the thermal transitions of the microgels. A simulated oral processing study indicated that the melt-in-the-mouth behavior of the hydrocolloid microgels could be made to be similar to that of starch granules by controlling the degree of cross-linking. This study may be useful for designing starch mimetics with improved texture-modifying properties and reduced-calories. Highlights: Hydrogels were formed by electrostatic complexation of gelatin and pectin. The hydrogels were cross-linked by different levels of glutaraldehyde. Cross-linking increased the rigidity and melting temperature of hydrogel pastes. These hydrogel particles may be used as starch mimetics or delivery systems.